Attitudes of Turkish academics towards the effects of digital journalism on shaping the political image - Malkawi, Omar Suleiman Saleh (Frontiers in Communication, 2025)
This study aimed to know the nature of the effects of digital journalism in shaping the political mental image of Turkish university professors. It also aimed to know the motives and reasons for their follow-up to digital journalism while following political events around the world. To achieve the objective of the study, the researcher relied on descriptive studies, and within its framework, he used the survey method, by applying the method of a public opinion poll with the sample, and distributed the electronic questionnaire to the study sample, which numbered (103) academic professors working in the universities according to the appropriate sample method. The study reached a set of results, the most important of which was that Most Turkish professors use digital journalism to follow current political events (42.7%). The reason for following political events through digital journalism is that it displays political events quickly (29.0%). Concerning the most prominent digital arts that contribute to the formation of the political mental image, Turkish professors pointed out that the technology of “news” (AVT = 4.01) followed by video technology where “video” (AVT = 3.91) is the most prominent digital arts in forming a political mental image. As for the most prominent element that digital journalism contributes to the formation of its image, the answer was “the image of political events” (Ort. 3.99) and the “parliament” (Org = 3.40) was the lesser victory. On the effects side, “cognitive effects” came first with an average (mean = 2.42), and the item with the highest average cognitive effects “gave me detailed information about the candidates” (AVT = 2.65). The least at all was to “give me different information about MPs” (mean = 1.96). The highest average emotional impact, according to Turkish academics involved in the study, was “saturate my cognitive curiosity about political issues and events” (AVT = 2.11). The statement with the highest average behavioral influences was “It enabled me to follow the speeches and reactions of heads of state in all activities and areas” (AVT = 2.40). Finally, a low positive correlation (0.307**) was found between the effects of the general political mental image and the image of the electoral candidate (p < 0.05), in addition to a low positive correlation between the digital journalism arts and the elements of the general political mental image, where the value of (p < 0.05) was found.